Toxicity and color reduction of reactive dyestuff RB21 and surfactant submitted to electron beam irradiation (Brazilian Journal of Radiation Sciences, 2021)
There is an unwelcome reaction between the coloring and the water during the dyeing procedure, a portion of the coloring agent is lost in the bathing and it will compose the final whole effluent. The high absorbance index is related to lost dyes and they also contribute with the toxic effects to the aquatic biota. In addition, these effluents contain large quantity of surfactants applied during dyeing baths, which also contribute to the high toxicity in these samples. The objective of this study was to evaluate electron beam irradiation technology, applied in samples of the Color Index Reactive Blue 21 (RB21) dye and in samples of surfactant nonionic and in order to reduce toxicity for both and for RB21, color reduction.  Among the objectives of the study there are the dye exhaustion degree, and some physic-chemical parameters. The acute toxicity assays were carried with Daphnia similis microcrustacean and the results for of dyestuff solution were: the irradiated samples with concentration of 0.61g.L-1 did not present significant results, the EC 50(%) value was to 58.26 for irradiated sample with 2.5kGy and EC 50(%) 63.59 for sample irradiated with 5kGy. The surfactant was more toxic than RB 21, with EC 50(%) value at 0.42. The color reduction reached 63.30% for the sample of the lowest concentration of effluent. There was a reduction of pH during irradiation.
Keywords: electron beam irradiation; toxicity; color reduction; reactive dyestuff; surfactant.